THE STATE OF THE SYMPATHETIC-ADRENAL SYSTEM IN THE DEVELOPMENT OF CARDIOVASCULAR DISEASES IN AN ORGANIZED POPULATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The health of the population is the most valuable benefit for the state, its economic and cultural development. It influences the level of mortality, total life expectancy, fertility, disability and, ultimately, determines the population [1].